Ritual Change in a Turkish Alevi Village - Thomas McElwain (Scripta Instituti Donneriani Aboensis, 1993)
This study is a documentation and analysis of change in ritual in the village of Sarilar, on the west bank of the Euphrates River near Yavuseli, Gaziantep. The research problem posed was identification of ritual change within the consultants' memory and some tentative ways of situating such change within the socio-economic context. The mysticism of the dervish lodge remains as a certain life attitude along with the new views of modernization that have been so well inculcated. Although modernization, at least in the Turkish Alevi context, tends to conflict with the mystical experience of the Bektashi dervish in some areas, a democratized inner core remains.